Quantitative Determination of Iodine in Commercial Salt Samples (Pragnya Sarathi, 2026)
Iodine is an essential for the synthesis of thyroid hormones, and it has biological significance for tissue growth and development. Iodine deficiency disorder and the Universal iodization of table salt are widely recognized as effective strategies for its prevention. The specific objective of this research is to analyze the iodine content (in ppm) of commercially available salt samples collected from the Pokhara Valley, Nepal, using iodometric titration and a Rapid Test Kit (RTK). Iodine content in common salt used in the Pokhara valley should be ensured to ensure people's health. About 20-30 grams of 60 different salt samples were collected from the Pokhara Valley in plastic pouches. 10 different salt samples from varied batches were purchased, and one salt sample with batch SRC-09 was studied for its iodine content over 11 days. Both the RTK and the titration methods were used. A repeated 11 days’ analysis of batch SRC-09 revealed a significantly higher iodine level than the reference value of 50 ppm (t = 3.76, p < 0.05), whereas batch wise analysis (n = 10) revealed a mean of 53.25 ± 16.89 ppm (range: 38.052–82.446 ppm) with no statistically significant difference between batches (p > 0.05). This consistency indicates that the manufacturing process and iodization were well controlled and uniform. The iodine content of common salt used in the Pokhara valley will help improve the quality of common salt from the authorized organization.